2018
DOI: 10.1016/j.psychsport.2018.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the acute psychological benefits of green exercise: An investigation of expectancy effects

Abstract: Objective: Exercising in the presence of a natural environment (termed green exercise) appears to provide addition benefits compared to indoor exercise. We assessed the impact of a green exercise promotional video on the acute psychological benefits of green-outdoor and indoor exercise. Design: Participants were randomly assigned to one of four groups. Two groups undertook green exercise (with one of these groups watching a green exercise promotional video). The other two groups undertook indoor exercise (with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…Unexpectedly, our control condition also showed reductions in negative affect. Study recruitment materials mentioned the restorative effects of environments, and participants may have expected relief by relaxing in the indoor control environment despite its lack of restorative elements (Flowers et al, 2018). Also, our college-aged sample of participants could have experienced relief from smartphone restriction.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, our control condition also showed reductions in negative affect. Study recruitment materials mentioned the restorative effects of environments, and participants may have expected relief by relaxing in the indoor control environment despite its lack of restorative elements (Flowers et al, 2018). Also, our college-aged sample of participants could have experienced relief from smartphone restriction.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived restoration, improved attention or cognition, stress reduction, and greater tolerance for pain were observed in each of approximately 50 experiments. Less commonly measured outcomes included exercise intensity (Akers et al, 2012;Calogiuri et al, 2018;Duncan et al, 2014;Flowers et al, 2018;Franěk & Režný, 2017;Rogerson & Barton, 2015;White et al, 2015;Wooller et al, 2015;Yeh et al, 2017); self-esteem, self-worth, or ego-depletion (Chow & Lau, 2015;Flowers et al, 2018;Johnsen & Rydstedt, 2013;Manzoni et al, 2008Manzoni et al, , 2009Swami, Barron, & Furnham, 2018;Swami, Pickering et al, 2018); self-regulation or impulsivity ( M. S. Berry et al, 2014Berry et al, , 2015Jenkin et al, 2018;Pretty et al, 2005;van der Wal et al, 2013); energy or vitality (Kjellgren & Buhrkall, 2010;Ryan et al, 2010;van den Berg et al, 2014); and aggression or prosocial behavior (Eggert et al, 2015;Nadkarni et al, 2017;Wang et al, 2017). One study found support for the positive effects of nature simulations on creativity (van Rompay & Jol, 2016).…”
Section: Quantity Of Workmentioning
confidence: 99%
“…The opposite interpretation is also possible-the positive effects of exercise and/or the environment were simply far larger than any influences of social setting. Although the design of the current study does not allow for conclusions about such environmental effects, previous research has frequently reported that greenspaces promote greater psychological improvements compared to exercise in built (real or simulated) or indoor environments [1,2,[4][5][6][7][8][9][10]14,32]. If environmental settings do indeed influence psychological outcomes in this way, considering the affective improvements observed, the current findings suggest that practitioners should not fear possible lessening impacts of group settings on the cited benefits of selecting nature/greenspace environments for boosting psychological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with equivalent forms of exercise in indoor or built environments and in laboratories while viewing environmental scenes [1], exercise in greenspaces has been shown to increase levels of directed attention [2][3][4], improve mood [4][5][6], reduce levels of frustration and arousal, increase levels of meditation [7], and improve self-reported mental health across 8 weeks [8]. Positive expectancy can enhance some of these acute effects of the environment [9]. Two popular psychological outcomes reported by research focussing on the importance of environmental setting are mood and self-esteem [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%